Effects of doping elements in ¢-FeSi2 prepared utilizing cast iron scrap chips - Nor Hairin, Assayidatul Laila; Nanko, Makoto; Takeda, Masatoshi (The Japan Institute of Metals and Materials, 2016)
In this work, the thermoelectric properties of p- and n-type ¢-FeSi2, prepared utilizing cast iron scrap chips, have been characterized by measuring the Seebeck coefﬁcient, electrical conductivity and thermal conductivity at temperatures ranging from room temperatures to 800°C. In a previous study, the upgrade recycling of cast iron scrap chips into ¢-FeSi2 thermoelectric materials was proposed as an eco-friendly and costeffective production process. By doping with different substitution concentrations of Co, Mn and Al, the conduction type and properties of ¢FeSi2 can be modiﬁed and improved using cast iron scrap chips as a starting material. The effects of the doping elements are discussed for preparing ¢-FeSi2 utilizing cast iron scrap chips. Cast iron scrap chips could be preferable as a starting material to replace pure Fe for n- and ptype ¢-FeSi2 thermoelectric materials. An optimum composition for n-type ¢-FeSi2 0.94C.I.-0.06Co-1.86Si shows that the largest ZT value of 0.22 occurs at 700°C, whereas for p-type ¢-FeSi2 0.92C.I.-0.08Mn-1.86Si, the largest ZT value of 0.17 occurs at 800°C.